The first engagement of partners in the E uprymna scolopes – V ibrio fischeri symbiosis is a two‐step process initiated by a few environmental symbiont cells - Melissa A. Altura; Elizabeth A. C. Heath‐Heckman; Amani Gillette; Natacha Kremer; Anne‐Marie Krachler; Caitlin Brennan; Edward G. Ruby; Kim Orth; Margaret J. McFall‐Ngai (Environmental Microbiology, 2013)
Summary We studied the E uprymna scolopes – V ibrio fischeri symbiosis to characterize, in vivo and in real time, the transition between the bacterial partner's free‐living and symbiotic life styles. Previous studies using high inocula demonstrated that environmental V . fischeri cells aggregate during a 3 h period in host‐shed mucus along the light organ's superficial ciliated epithelia. Under lower inoculum conditions, similar to the levels of symbiont cells in the environment, this interaction induces haemocyte trafficking into these tissues. Here, in experiments simulating natural conditions, microscopy revealed that at 3 h following first exposure, only ∼ 5 V . fischeri cells aggregated on the organ surface. These cells associated with host cilia and induced haemocyte trafficking. Symbiont viability was essential and mutants defective in symbiosis initiation and/or production of certain surface features, including the M am7 protein, which is implicated in host cell attachment of V . cholerae , associated normally with host cilia. Studies with exopolysaccharide mutants, which are defective in aggregation, suggest a two‐step process of V . fischeri cell engagement: association with host cilia followed by aggregation, i.e. host cell–symbiont interaction with subsequent symbiont–symbiont cell interaction. Taken together, these data provide a new model of early partner engagement, a complex model of host–symbiont interaction with exquisite sensitivity.

Functional Characterization of a Glucosyltransferase Specific to Flavonoid 7-O-Glucosides from Withania somnifera - R. J. Santosh Kumar; Ruby; Somesh Singh; Prashant D. Sonawane; R. K. Vishwakarma; B. M. Khan (Plant Molecular Biology Reporter, 2013)

Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Prashant Sonawane; Somesh Singh; Uma Kumari; Ruby; Bashir M. Khan (Physiology and Molecular Biology of Plants, 2013)

Synthesis of piperazinyl benzothiazole/benzoxazole derivatives coupled with 1,3,4-oxadiazole-2-thiol: novel hybrid heterocycles as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Mohana Rao Katiki; Lekshmi R. Nath; Ruby John Anto (Medicinal Chemistry Research, 2013)

Erratum to: Floral diversity during Plio-Pleistocene Siwalik sedimentation (Kimin Formation) in Arunachal Pradesh, India, and its palaeoclimatic significance - Mahasin Ali Khan; Ruby Ghosh; Subir Bera; Robert A. Spicer; T. E. V. Spicer (Palaeobiodiversity and Palaeoenvironments, 2013)

Rationale for treating primary Sjögren’s syndrome patients with an anti-CD6 monoclonal antibody (Itolizumab) - Christelle Le Dantec; Ruby Alonso; Tinhinane Fali; Enrique Montero; Valérie Devauchelle; Alain Saraux; Jacques-Olivier Pers; Yves Renaudineau (Immunologic Research, 2013)

Impacts of enhanced CCN on the organization of convection and recent reduced counts of monsoon depressions - T. N. Krishnamurti; Andrew Martin; Ruby Krishnamurti; Anu Simon; Aype Thomas; Vinay Kumar (Climate Dynamics, 2013)

Molecular Cloning, Biochemical Characterization, and Differential Expression of an Acetyl-CoA C-Acetyltransferase Gene (AACT) of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Ruby; Somesh Singh; Prashant D. Sonawane; Sameer Srivastava; Uma Kumari; R. J. Santosh Kumar; Bashir M. Khan (Plant Molecular Biology Reporter, 2013)

Genetic variants associated with breast cancer risk for Ashkenazi Jewish women with strong family histories but no identifiable BRCA1/2 mutation - Erica S. Rinella; Yongzhao Shao; Lauren Yackowski; Sreemanta Pramanik; Ruth Oratz; Freya Schnabel; Saurav Guha; Charles LeDuc; Christopher L. Campbell; Susan D. Klugman; Mary Beth Terry; Ruby T. Senie; et al. (Human Genetics, 2013)

Effect of angiotensin II on spatial memory, cerebral blood flow, cholinergic neurotransmission, and brain derived neurotrophic factor in rats - Santoshkumar Tota; Ruby Goel; Shakti Deep Pachauri; Rajasekar N.; Abul Kalam Najmi; Kashif Hanif; Chandishwar Nath (Psychopharmacology, 2013)

Interaction of marine Streptomyces compounds with selected cancer drug target proteins by in silico molecular docking studies - Amulya Ruby Lankapalli; K. Kannabiran (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Effects of agricultural pesticides on the health of Rana pipiens frogs sampled from the field - M. S. Christin; L. Ménard; I. Giroux; D. J. Marcogliese; S. Ruby; D. Cyr; M. Fournier; P. Brousseau (Environmental Science and Pollution Research, 2013)

Treatment of hydrocarbon contamination under flow through conditions by using magnetite catalyzed chemical oxidation - M. Usman; P. Faure; C. Lorgeoux; C. Ruby; K. Hanna (Environmental Science and Pollution Research, 2013)